The game of life [games] - Klamer, Reuben (Hasbro, 2021)
In The Game of Life game players choose a path and move their car tokens around the gameboard from Start to Retirement. Who is headed for wealth and fortune? Pick a path for a life of action, unexpected surprises, and dream vacations, but spend cash wisely because the wealthiest player at the end wins the game.